Quantitative Score for Assessing the Quality of Feature Rankings (Informatica, 2018)
Feature ranking is a machine learning task that is related to estimating the relevance (importance) of individual features in a dataset. Relevance estimates can be used to induce an ordering of the features from a dataset, also called a feature ranking. In this paper, we consider the problem of the evaluation of different feature rankings. For that purpose, we propose an intuitive evaluation method, based on iterative construction of feature sets and their evaluation by learning predictive models. By plotting the obtained predictive performance of the models, we obtain error curves for each feature ranking. We then propose a scoring function to quantitatively assess the quality of the feature ranking. To evaluate the proposed method, we rst dene a synthetic setting in which we analyse the method and investigate its properties. By using the proposed method, we next perform an empirical comparison of several feature ranking methods on datasets from different domains. The results demonstrate that the proposed method is both appropriate and useful for comparing feature rankings of varying quality.